The ADDIE Analysis Phase in Arabic Module Design for Ugandan Adult Muallaf(UAM) - Kirembwe Rashid Abdul Hamed; Mohd Aderi Che Noh; Hayati binti Ismail; Hishomudin Ahmad; Noor Azizi Ismail; Adibah Sulaiman @ Mohamad; Mohammad Najib Jaffar; Siti Rosilawati binti Ramlan; Sakinah binti Ahmad; Sarifah Nurhanum binti Syed Sahuri; Mardhiah Binti Yahaya (Penerbit USIM, 2024)
VOL. 35 NO. 01